Obligation and Value in the Phenomenological Philosophy of Law (Edmund Husserl’s Works) - Zirk-Sadowski, Marek (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Basing upon the two fundamental works of Edmund Husserl (Logische Untersuchungen and Idee) the author presents Husserl’s concepts of obligation and value according to the phenomenological reduction and the theory of the constitution of objects. Within the context of reduction the conclusions are: as according to Husserl the substance of normative sentences in valuation, the problems of obligation may be reduced to problems of valuation. The sense (Sinn) proves to be fundamental, prior to the existence. If anything should come to being in the ontological meaning it must become a moment of intentional life of consciousness. That is why the object and value exist in the same way but are only different names of some units of sense. The difference becomes clearer on a ‘higher’ level when they are characterised as intentional objects and the intentional experience directed towards them. Contrary to objects we can be directed towards values in a perceptible way (erfassenseise). The experience of value is always a based act. These acts are analysed against the background of noesis and noema. On the stage of constitution of the world it appears however that the substance of morality may be cognised with a personalistic attitude.